Differences of Anthropometric Characteristics and Cardiovascular Endurance between U18 Football Players - Latif, Rozita Abdul; Ruslan, Muhammad Hasif; Linoby, Adam; Bin Mohamed, Muhammad Noor (Universitas Pendidikan Indonesia, 2021)
The main purpose of this study was to examine the differences of anthropometric characteristics and cardiovascular endurance of under 18 football players. Thirty-six football players were involved as respondents. Data were collected using Bioelectrical Impedance Analysis monitor scan for evaluating anthropometric characteristics, whereas Yo-Yo Intermittent Recovery Test Level 1 was used for evaluating cardiovascular endurance. Overall results showed that U18 Akademi Mokhtar Dahari football players had a greater performance compared to Zon Keramat football players. Related to BMI, there was a slight difference between both groups. The obtained results showed that there was no significant difference in height (p=0.14), trunk (p=0.14), and legs (p=0.84). However, there were significant differences in weight (p=0.01) and Body Mass Index (p=0.02).Â There were also significant differences in the result of yoyo test, where Akademi Mokhtar Dahari football players had a better performance (p=0.00). It concludes that the Â Akademi Mokhtar Dahari football players had better results compared to Zon Kermat football players.